Determination of optimum temperature and pH of the antimicrobial activity of curcumin using Response Surface Methodology RSM - Baculna, Mark Vincent Balano
The study was conducted to determine the optimum temperature and pH on the antimicrobial activity of curcumin extract from turmeric (Curcuma Longa L.) using the Response Surface Methodology (RSM).